2015
DOI: 10.1246/cl.150299
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Helicity Induction and Memory in a Poly(biphenylylacetylene) Bearing an Ester Group and Its Application to a Chiral Stationary Phase for High-performance Liquid Chromatography

Abstract: An optically inactive poly(biphenylylacetylene) bearing an ester group at the 4¤-position of the pendants formed a preferredhanded helical conformation and biased axial chirality in the pendants through a noncovalent interaction with a chiral alcohol, both of which were retained (memorized) even after removal of the chiral alcohol. The chiral stationary phase for high-performance liquid chromatography, prepared by coating the polymer with macromolecular helicity memory on silica gel, showed good chiral recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…Although poly‐ Ac‐c exhibited strong ICDs in n ‐hexane and MCH, the ICD intensity significantly decreased in toluene and no detectable ICD signal was observed in THF and chloroform (Figure S12), probably due to very weak interactions between the poly‐ Ac‐c and the chiral alcohol 1 in these solvents. A similar tendency was also observed for the poly‐ MOM 's . Since poly‐ Ac‐b is insoluble in MCH and n ‐hexane, but soluble in 1 , we then measured the CD spectrum of poly‐ Ac‐b in ( R )‐ 1 , which showed intense, but slightly weak Cotton effects (Figure (v)) when compared to those of poly‐ Ac‐c , indicating a preferred‐handed helix formation of poly‐ Ac‐b in ( R )‐ 1 whose helix‐sense excess may be slightly lower than that of poly‐ Ac‐c .…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Although poly‐ Ac‐c exhibited strong ICDs in n ‐hexane and MCH, the ICD intensity significantly decreased in toluene and no detectable ICD signal was observed in THF and chloroform (Figure S12), probably due to very weak interactions between the poly‐ Ac‐c and the chiral alcohol 1 in these solvents. A similar tendency was also observed for the poly‐ MOM 's . Since poly‐ Ac‐b is insoluble in MCH and n ‐hexane, but soluble in 1 , we then measured the CD spectrum of poly‐ Ac‐b in ( R )‐ 1 , which showed intense, but slightly weak Cotton effects (Figure (v)) when compared to those of poly‐ Ac‐c , indicating a preferred‐handed helix formation of poly‐ Ac‐b in ( R )‐ 1 whose helix‐sense excess may be slightly lower than that of poly‐ Ac‐c .…”
Section: Resultssupporting
confidence: 65%
“…The isolated poly‐ Ac‐c dissolved in MCH at −10 °C showed an almost identical CD spectrum to that observed before isolation (Figure (ii) and (iii)). Therefore, it was revealed that a preferred‐handed helicity induced in poly‐ Ac‐c was retained after complete removal of ( R )‐ 1, as is the case for the poly‐ MOM 's . The stability of the helicity memory of the poly‐ Ac‐c was investigated by following the CD intensity changes in MCH at −10 and 25 °C with time; its half‐life periods ( t 1/2 ) were estimated to be ~24 h and 10 min, respectively (Figure ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet (UV) and polarimetric (PM) detectors were used for the detection and identification of the peaks, respectively. As shown in Figure 7c, the different enantiomers of 16 were eluted with retention times of t1 ((-)-enantiomer) and t2 ((+)-enantiomer), The chiral recognition abilities of poly-2S, h-poly-2S and h-poly-(2S 0.36 -co-3 0.64 ) as CSPs for HPLC were evaluated using the various racemic compounds with different functional groups (5-12) including axial (13,14) or planar (15) chiral compounds as well as chiral metal complexes (16)(17)(18) (Figure 6). The packing materials were prepared by coating macroporous silica gel (particle size 7 µm, pore size 100 nm) with DMF solutions of the corresponding polymers [49].…”
Section: Resultsmentioning
confidence: 99%
“…Optically active poly(phenylacetylene)s with a preferred-handed helicity have been prepared [16] and some of these systems have been reported to exhibit good chiral recognition abilities as CSPs for HPLC because of their preferred-handed helical conformation [17][18][19][20][21][22][23][24][25][26]. However, very few optically active poly(diphenylacetylene)s have been prepared to date, which has limited research towards evaluating the scope and efficiency of the chiral recognition abilities of these materials [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%